Evaluation of degree centrality and neurological outcomes in patients with herpes simplex encephalitis - Liu, Dongzhi; Liu, Xiaoyu; Zhu, Dong; Chen, Yuanfei; Yan, Jueyue; Zhang, Jingchen; He, Hongqin (Frontiers in Neurology, 2025)
ObjectiveThis study aimed to investigate the association between changes in cerebral degree centrality (DC) and clinical outcomes in patients with herpes simplex encephalitis (HSE).MethodsAll participants underwent functional magnetic resonance imaging (fMRI), and DC analysis was used to identify voxels that showed changes in whole-brain functional connectivity with other voxels. DC was evaluated using the fMRI graph method, and comparisons between HSE patients and controls were performed. The National Institutes of Health Stroke Scale (NIHSS), the Glasgow Coma Scale (GCS), and the modified Rankin Scale (mRS) were assessed for all HSE patients.ResultsA total of 70 HSE patients and 76 controls were included in our data analysis. In the HSE group, DC values were increased in the right thalamus, the left lingual gyrus, and the right hippocampus, while they were decreased in the left insula (all p < 0.001). In our HSE cohort, the NIHSS score was significantly associated with DC changes in the right thalamus (r = −0.282, p = 0.018), the left insula (r = −0.301, p = 0.011), the left lingual gyrus (r = −0.270, p = 0.024), and the right hippocampus (r = 0.238, p = 0.047). We also found that DC changes in the right thalamus (r = 0.241, p = 0.044), the left insula (r = 0.254, p = 0.034), and the left lingual gyrus (r = 0.275, p = 0.021) were significantly associated with higher GCS scores. After 90 days, neurological deficit was assessed via the mRS; we found that mRS was associated with the right thalamus (r = −0.272, p = 0.023) and the left lingual gyrus (r = −0.270, p = 0.024).ConclusionCerebral intrinsic connectivity changes as assessed by DC in HSE were associated with neurological deficits (as assessed by the NIHSS score), level of consciousness (as assessed by the GCS score), and functional disability. Our findings provide novel insights into the neural mechanisms underlying HSE-related neurological deficits and inform the development of targeted therapeutic interventions.